MENAKAR EFEKTIVITAS PENGAWASAN OMBUDSMAN DAN MAL PELAYANAN PUBLIK DALAM MENINGKATKAN KEPATUHAN PELAYANAN PUBLIK DI SUMATERA BARAT - Andi Setyo Pambudi (STISIP Widyapuri Mandiri, 2026)
Persistent challenges in public service delivery across West Sumatra, reflected in low compliance scores and increasing reports of maladministration, reveal a significant gap between constitutional mandates and local implementation. Although external oversight by the Ombudsman and reform initiatives such as Public Service Malls (MPP) have been introduced, their effectiveness remains inconsistent and underexamined. This study addresses a critical research gap by systematically analyzing the relationship between Ombudsman oversight, regional disparities in service compliance, and alignment with national development priorities. The urgency of this research is reinforced by Indonesia’s RPJMN 2020–2024, which places public service transformation at the core of governance reform. The study aims to evaluate the performance of Ombudsman RI West Sumatra, map compliance variations, assess the implementation of MPP, and propose data-driven policy strategies. Key recommendations include enhancing the enforceability of Ombudsman recommendations through integration with regional performance indicators, standardizing MPP service packages, and improving transparency through public dashboards. Risk-based supervision and inter-regional mentoring are also proposed to address compliance gaps. By embedding these reforms within national planning cycles, external oversight can evolve into a strategic instrument for inclusive governance and improved public service delivery